Accelerating IP routing algorithm using graphics processing unit for high speed multimedia communication - Uddin, Jia; Jeong, In-Kyu; Kang, Myeongsu; Kim, Cheol-Hong; Kim, Jong-Myon (© 2016 Springer New York LLC, 2016)
This article was published in Multimedia Tools and Applications [© 2014, Springer Science+Business Media New York.] and the definite version is available at :http://dx.doi.org/10.1007/s11042-014-2013-3 The Journal's website is at: http://link.springer.com/article/10.1007/s11042-014-2013-3